Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide